(untitled) (Research, Society and Development, 2025)
Technological advances have made it possible to test new chemical components and discover their mechanisms of action, which has benefited various industries, including pharmaceuticals, chemicals, medicine, and especially food. These new tests have made it possible to identify toxicity and possible side effects so that the products manufactured have the least possible interaction with the human body. In this sense, the present study aims to assess the organic risks associated with the use of tartrazine dye through an integrative review. It can be said that the use of dyes in candies, snacks, and seasonings was an important advance in the food industry. A famous dye, known as tartrazine, is used to add yellow color, and its exposure to the human body has been associated with health damage due to the dye’s possible carcinogenic potential. In most of the articles analyzed, it is possible to see that tartrazine has a mutagenic effect, mainly perceived in the long term, but the pathophysiology involved in cancers that may result from the consumption of additives is not yet well defined. Thus, it is possible to conclude that it causes DNA damage and changes in cell turnover. The cancers most commonly observed in the literature were colon, stomach, and bladder cancer, but breast and thyroid cancer also appear with less frequency.